EXPERIMENTAL STUDY OF SPIN-ORBIT INTERACTION IN INTERMETALLIC COMPOUNDS OF THE Er-In SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Normal, R0, and anomalous, RS, components of the Hall coefficient are determined from the results of experimental investigations of temperature dependences of the Hall coefficient, magnetic susceptibility, and specific electrical resistance for intermetallic Er2In, ErIn, and Er3In5 compounds.